STRATEGI GURU DALAM MENUMBUHKAN MINAT BELAJAR SISWA MELALUI PENDEKATAN KONTEKSTUAL PADA MATERI BANGUN DATAR KELAS 1 SDN CUKIR 2 JOMBANG - Elly Ziyadatul Ilmi; Claudya Zahrani Susilo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe teachers' strategies in fostering students' learning interest through a contextual approach in plane geometry material for first-grade students at SDN Cukir 2 Jombang. The background of this research is based on the low learning interest of students due to the abstract nature of geometry concepts at the elementary level. Therefore, a contextual approach is applied to relate learning material to students’ real-life experiences. This research uses a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The subjects of this study are the teacher and first-grade students. The results show that teachers implement strategies such as using concrete media, linking material to the surrounding environment, applying active learning methods, and providing motivation and appreciation. These strategies successfully increase students' enthusiasm, participation, and understanding of plane geometry concepts. Thus, the contextual approach is effective in enhancing students’ learning interest in elementary school, especially in abstract subjects.